Laboratory methods for the in vitro study of drug metabolism - Singh, Ritu (Henry Stewart Talks, 2021)
Major classes of drug-metabolizing enzymes, Co-factor requirement for in vitro incubations, Practical aspects of conducting in vitro assays, In vitro assays conducted during drug discovery and development, Clearance estimation, Kinetic parameter determination, Enzyme inhibition, Enzyme induction, Enzyme reaction phenotyping